(3fRgI GdCfXGQ (B( (3aj HjGf GdfMGQjQ GdcHGQ (B)s - (3GdebQGFj , jMji Hf eMeO Hf MSf Hf MejO GdMGQKj GdePMLj,J (B990 (3g` s ((3Ydi Hf jMji Hf LGHQ GdMHTi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CdgefG eYQaI GdCMcGe hHYO aEfi deG MLHJ MLI GdESdGe Edi HjJ Gddg GdMQGe , SCdfi gfGdc ef jQjO GdESJQTGO Yf eSGFd YdejI s
(3BNQgG (B:s
(3hdfNJe Pdc HeG jNJe Hg CeKGd eGgfGdc ef GdbH GdebQHGJ ceG PcQg GdOejQi ai MjGI GdMjhGf bGd GdeDda hcGf GdaQGZ ef JCdja Pdc s
(3CJe JCdja ai TgQ QLH SfI (B975(3g` hgh ai Cgd GdHjJ hTjYJges
(3cJHJ JYdje eged GdfbX CMjGfkGs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs